Peritoneal drainage: tecnique and indications - Arriaga, Pedro; Cazabán, Luis A; Sáez, Hugo (Cirugía del Uruguay, 1972)
The use of peritoneal drainage is analyzed, evaluating its advantages and disadvantajes. It ,should be utilized cautiosly since it is not inocous. The paper revises its general indications as a guidelíne for particular cases. The advantages of the rubber tube are pointed out. General aspects in its technique and employment are hased in the anatomical characteristics of the peritoneum and in the physiological cariations of its tension system.